On Hesitant Fuzzy MA-Ideals - Ali Abbas AL- Jebber (Genius Journals, 2023)
In this research, we study the definition of Hesitant Fuzzy set, with some properties. We introduced the Hesitant fuzzy ideal of a ring with the result equivalent to the definition. We proved some of the characteristics for Hesitant fuzzy set and Hesitant fuzzy ideal. Also, we proved the image and the inverse image of the Hesitant fuzzy ideal with respect the homomorphism between two rings. We studied the level set and then proved that it is ideal of ring through Hesitant Fuzzy
Keywords: characteristics; definition; equivalent; fuzzy